Region Requirements for Life Insurance in Uzbekistan and Regressional Analysis of Factors Affecting It (Texas Journal of Multidisciplinary Studies, 2022)
The article notes that insurance is an integral part of the financial infrastructure a market economy and an important factor in ensuring the sustainable development of the economy as a whole and the role of the insurance in ensuring the continuity of production and protection of the population from accidents in a market economy. In particular, the current state of life insurance in Uzbekistan was analyzed and suggestions and conclusions were made on the direction of development.